An Expanded Ribosomal Phylogeny of Cyanobacteria Supports a Deep Placement of Plastids - Moore, Kelsey R.; Magnabosco, Cara; Momper, Lily; Gold, David A.; Bosak, Tanja; Fournier, Gregory P. (Frontiers in Microbiology, 2019)
Plastids originated as a cyanobacterium that was engulfed by the ancestral lineage of the major photosynthetic eukaryotic group (Archaeplastida). Although the ancestral cyanobacterial lineage of these organelles is not known, Archaeplastida still retain remnants of the ancestral cyanobacterial genome, inherited through the plastid. As a result, it should be possible to constrain the origin of plastids within Cyanobacteria through phylogenetic analyses. To date, such phylogenetic studies have produced conflicting results and two competing hypotheses: 1) plastids diverged relatively recently in cyanobacterial evolution and are most closely related to nitrogen-fixing cyanobacteria, or 2) plastids diverged early in the evolutionary history of cyanobacteria, before the divergence of most crown group lineages. Here, we differentiate between these competing hypotheses using a phylogenetic analysis of ribosomal proteins from an expanded data set of cyanobacterial genomes and representative plastid sequences. Our results robustly support a deep rooting of the plastid ancestor lineage as sister to Gloeomargarita, with a divergence from other cyanobacterial groups before that of Pseudanabaena. The results of our study are especially important for future molecular clock studies, which are highly dependent upon tree topologies and distances for modeling accurate branch rates. The deeper rooting of plastids in our phylogenies and increased cyanobacterial sequence coverage provide an improved tree topology and enable the use of well-informed fossil calibrations.